2005
DOI: 10.1038/oby.2005.51
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Motor and Sensory Functions in Obesity

Abstract: PARK, MOO-IN AND MICHAEL CAMILLERI. Gastric motor and sensory functions in obesity. Obes Res. 2005;13: 491-500. In the vast majority of affected individuals, obesity involves overconsumption of food relative to calorie requirements. The sensory function of the stomach may play a key role in the cessation of food ingestion. This sensation of the stomach is, in part, determined by its motor functions, such as tone and compliance and the rate of emptying. However, studies of gastric emptying in normal-weight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 75 publications
4
58
0
Order By: Relevance
“…Another possible mechanism for an effect of CM3 could be through an increase in the feeling of satiation, because of a sheer volume effect. It has been reported that gastric distention induces feelings of fullness and satiation (26). In specific, chemoreceptors and mechanoreceptors in the stomach wall signal satiation through vagal and splanchnic nerves (43).…”
Section: Control Cm3mentioning
confidence: 99%
“…Another possible mechanism for an effect of CM3 could be through an increase in the feeling of satiation, because of a sheer volume effect. It has been reported that gastric distention induces feelings of fullness and satiation (26). In specific, chemoreceptors and mechanoreceptors in the stomach wall signal satiation through vagal and splanchnic nerves (43).…”
Section: Control Cm3mentioning
confidence: 99%
“…Gastric parameters such as stomach distention are another important source of negative feedback (37). Feelings of hunger and satiety have long been associated with gastric motor and sensory functions, and more importantly, gastric and intestinal signals have been reported to interact (14,18,42).…”
mentioning
confidence: 99%
“…Although hyperglycaemia has been shown to induce proximal gastric relaxation [7] , the absolute increase in blood glucose level was small and therefore unlikely to have contributed significantly to the subsequent response. The diabetic patients had a higher BMI than the healthy volunteers, however no differences in either proximal gastric volume or compliance have been reported between obese and lean subjects [27,28] . Thus, a higher BMI in diabetic patients seems unlikely to have contributed to the differences in proximal gastric motility.…”
Section: Discussionmentioning
confidence: 83%